G243 Dr isaac henry gosset (1907–1965) founder of northamptonshire paediatrics. (27th April 2015) - Ackland, F; Barnes, N; Breene, R; Chadwick, C; Chandrakantha, L; Collinson, J; Davis, T; Dominic, M; Gupta, S; Hewertson, J; Issa, M; Jayaseelan, S; et al.
Abstract : Dr Isaac Henry Gosset was the first consultant paediatrician for Northampton.His Northamptonshire responsibilities included both general and neonatal care also included hospitals in North Oxfordshire. As a boy he had great gifts as an engineer, reportedly making his own television. Having trained in Oxford and St Thomas' London, he initially tried general practice before starting in paediatrics. After serving in the RAF, he did a further year of postgraduate training at Great Ormond Street Hospital before being appointed to Northampton General Hospital in 1947 In neonatal practice he designed the 'Gosset icterometer, ' made of perspex allowing an accurate estimation of serum bilirubin without requiring a blood test. 4 Icterometers, although at that time an important advance, and used for many years afterwards, have been superseded and are no longer supported by current NICE guidelines 5 He died of a coronary thrombosis aged only 57 Shortly before his death, he designed the neonatal unit at Northampton. In this he was a generation ahead of his time which even in the 1970's saw such units as being restricted to teaching centres. 6 The Gosset Neonatal unit is named after him and working to this day. On the 50 th anniversary of his untimely death, we his consultant successors in Northampton dedicate this presentation to his life and memory. References: Isaac Henry Gosset Munk's Roll Royal College of Physicians http://munksroll.rcplondon.ac.uk/Biography/Details/1835 accessed November 13th 2014. Obituary. Brit Med J . 1965;1 :867–8 The London Gazette 4th October 1940, Commissioned as a flight lieutenant in the RAF Medical Branch military number 84831 https://www.thegazette.co.uk/London/issue/34960/page/5840/data.pdf accessed November 21st 2014 Gosset IH. A Perspex Icterometer for neonates. Lancet 1960;275(7115):87–88 Neonatal Jaundice. NICE clinical guideline 98 National Institute for Heath and Care Excellence May 2010, p 10 Court D, Jackson A. Paediatrics in the seventies. Developing the Child Health Services . Oxford University Press; 1972, pp. 45–46